An Analysis of the Extent of Social Inclusion and Equity Consideration in Malawi's National HIV and AIDS Policy Review Process - Mathews Junior Chinyama; Malcolm MacLachlan; Joanne McVeigh; Tessy Huss; Sylvester Gawamadzi (Kerman University of Medical Sciences, 2018)
Background Equity and social inclusion for vulnerable groups in policy development processes and resulting documents remain a challenge globally. Most often, the marginalization of vulnerable groups is overlooked in both the planning and practice of health service delivery. Such marginalization may occur because authorities deem the targeting of those who already have better access to healthcare a cheaper and easier way to achieve short-term health gains. The Government of Malawi wishes to achieve an equitable and inclusive HIV and AIDS Policy. The aim of this study is to assess the extent to which the Malawi Policy review process addressed regional and international health priorities of equity and social inclusion for vulnerable groups in the policy content and policy revision process. Methods This research design comprised two phases. First, the content of the Malawi HIV and AIDS Policy was assessed using EquiFrame regarding its coverage of 21 Core Concepts of human rights and inclusion of 12 Vulnerable Groups. Second, the engagement of vulnerable groups in the policy process was assessed using the EquIPP matrix. For the latter, 10 interviews were conducted with a purposive sample of representatives of public sector, civil society organizations and development partners who participated in the policy revision process. Data was also collected from documented information of the policy processes. Results Our analyses indicated that the Malawi HIV and AIDS Policy had a relatively high coverage of Core Concepts of human rights and Vulnerable Groups; although with some notable omissions. The analyses also found that reasonable steps were taken to engage and promote participation of vulnerable groups in the planning, development,implementation, monitoring and evaluation processes of the HIV and AIDS Policy, although again, with some notable exceptions. This is the first study to use both EquiFrame and EquIPP as complimentary tools to assess the content and process of policy. Conclusion While the findings indicate inclusive processes, commitment to Core Concepts of human rights and inclusion of Vulnerable Groups in relation to the Malawi HIV and AIDS Policy, the results also point to areas in which social inclusion and equity could be further strengthened.